South Korea’s Soft Power to China: Taking K-pop as an Example - Zhang, Leyi (Transactions on Social Science, Education and Humanities Research, 2024)
With the deepening of globalisation and the rapid development of information technology, the competition for soft power among countries has become more intense. Against this background, South Korea, as an Asian country, has rapidly risen over the past few decades, becoming one of the models of possessing strong soft power. The origin and development of South Korea’s soft power success as well as its influence and inspiration on China is undoubtedly a subject of great interest. This paper employs literature research method and data analysis to explore the impact of South Korean soft power on China. By doing so, it aims to provide valuable insights for China’s cultural export, international image building, and global interactions, enabling China to effectively play its role on the international stage. South Korea's journey in harnessing its soft power, particularly in the domains of K-pop, cinema, and technology, has propelled it to the forefront of global cultural influence. Understanding how it has achieved this and how China can draw lessons from this success story is essential in an increasingly interconnected world.